ANALISIS PENGARUH PENGGUNAAN MEDIA SOSIAL TIKTOK PADA PERUBAHAN PERILAKU SISWA SEKOLAH DASAR DI JORONG PASAR SIJUNJUNG NAGARI SIJUNJUNG - Putri, Dina; Erningsih, Erningsih; Melia, Yenni (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2023)
Behavior change is a process of change experienced by a person based on what is obtained and learned through various sources such as family, friends, environment or himself. The process of change in a person is determined by his conditions and needs. The use of the tiktok application in elementary school-age children will definitely have an impact on changing children's behavior because basically children have the trait of imitating. The formulation of the problem in this research is how to change the behavior of elementary school-aged children using the tiktok application in Jorong Pasar Sijunjung Nagari Sijunjung, and the purpose of this study is to describe changes in the behavior of elementary school-age children as users of the tiktok application in Jorong Pasar Sijunjung Nagari Sijunjung. The theory used in this study is the social action theory proposed by Max Weber. This research is a qualitative research using descriptive method. Data collection methods are through interviews and observation. Interviews were conducted with 22 informants, the informants in this study were taken using a purposive sampling technique. The data analysis model is through the stages of data collection, data reduction, data presentation and drawing conclusions. From the results of the study it was revealed that elementary school-age children first recognized the tiktok application from their closest environment such as parents, siblings or even peers. The tiktok application has an impact on changing children's behavior, changes that occur in children can be positive and negative changes. The impact of positive behavior changes such as increasing children's creativity in making a work, increasing children's self-confidence, increasing children's interest in learning. Negative behavior changes such as a child's lack of interest in doing homework, changes in speech, and the child's timing is not effective. It can be concluded that the impact of changing the behavior of elementary school-age children in using the tiktok application has not only positive but also negative impacts, so parental supervision is needed.